Measuring the impact of oil price fluctuation on the budget Deficit base in Iraq for the period (2003-2020) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract                 The research dealt with a studying the impact of oil price fluctuations on one of the rules of financial discipline, which is the rule of budget deficit in the Iraqi economy for the period (2003-2020) as it is one of the quarterly economies that rely mainly on volatile oil revenues that fluctuate with oil prices in global markets, and therefore the general budget suffers. from The state of instability and then the government resorts to borrowing for a long time . this deficit in the general budget and increase the debt burden in the public debt.The research aim to measure and study the impact of oil price fluctuations on the base. The budget balance in the  Iraqi economy for the period 2003-2020 and the role of this rule mitigating the negative impact of those fluctuations on the Iraqi economy.The Autoregressive Model (ARDL) was used to found a direct effect between the two variables ( oil price fluctuations and the budget deficit rule), And take advantage of the financial savings and the establishment of sovereign funds in order to use  and the continued financing of development plans. The research reached a set of conclusions, the most important of  which is the existence of a direct relationship between oil price fluctuations and the budget deficit base. Therefore, research must follow procedures aimed at increasing the level of discipline in order to achieve budget stability and not exceed the 3% deficit, and the possibility of benefiting from oil financial savings ( during the period of high oil prices). By creating sovereign fouds that can be used during times of crises that occur as a result of low oil prices to ensure the sustainability and continued financing of economic development plans